Effect of Atorvastatin on Cerebral Vasomotor Reactivity in Patients with Ischemic Stroke - Mohammad Reza Amiri-Nikpour (Journal of Global Pharma Technology, 2017)
Background and Objectives: statins are effective in the prevention of atherosclerotic plaques formation. According to the observed effects of statins in improving regional blood flow and their protective role against brain stroke, it seems that some of these effects are involved in improving the cerebrovascular reactivity in patients. The objective of this study was to evaluate the effect of statins on cerebrovascular reactivity in patients with ischemic stroke. Methods: This study is a single-blinded randomized clinical trial conducted on 180 patients referred to Imam Khomeini Hospital of Urmia in Iran. The patients were hospitalized due to ischemic stroke and they were included in study based on inclusion and exclusion criteria. Then, they were randomly assigned into control and intervention groups. Intervention group patients, in addition to receiving common drug treatments, were treated with daily atorvastatin 80 mg for three consecutive months and their cerebrovascular reactivity was measured and compared on the arrival, seventh and ninetieth days by Transcranial Doppler(TCD). Finally, results were analyzed using spss20 software. Results: In this study, 180 patients with ischemic stroke were examined, which some of them were excluded from study due to lack of referring for follow-up or death after study. Finally, 75 patients were assigned to intervention group and 72 of them were included in control group. The mean of variables Breath holding index (BHI) and Apnea Mean flow velocity(MFV) in patients of intervention group increased significantly compared to the that in patients of control group (P = 0.049, P = 0.003). According to the results, the difference in increase of mentioned variables in the seventh day, and especially in the ninetieth day, after taking atorvastatin was more prominent, which it can be justified by mechanism of drug. Rest MFV patients in any of the two groups showed no significant difference, which suggests lack of the drug effect on the Rest MFV patients. Conclusion: This study found evidence of significant improved cerebrovascular reactivity of patients after taking Atorvastatin, which this process is independent from benefits caused by reduced blood fat following taking statins and it is created as result of self-regulation improvement of endothelial nitric oxide synthase enzyme.Keywords: Stroke, Atorvastatin, Cerebrovascular reactivity, BHI.